Justiça por aplicativo, acesso à justiça e pandemia: uma análise das ações da defensoria pública do estado do amazonas na cidade de Manaus/Am - Peixoto, Keitte Helen de Lima (Brasil, 2023)
This study presents actions and strategies of Amazon Public Defender (DPE-AM) to execute their ordinary activities in the COVID -19 pandemic period, mostly in front of the segregation and suspension of work in person. This public administration management model had to adjust to a new context and reality, mainly by integration, adaptation and modeling of services from the new technology. Including technology in the dispensation of justice it's not a new thing in the Brazilian jurisdiction. However, the change movement had been operating gradually, mainly when the justice processes were virtualized, but when COVID-19 came, the implementation of other tools were done in a hurry, considering the urgency and needs of service maintenance, like in the case of the DPE-AM. So, in this research, it was analyzed the data provided by DPE-AM and interviews with social actors that work in the comment service, and we intend to know the adaptation process and the inclusion of the new technologies as alternative for the continuity of ordinary activities in the DPE-AM, consequently, we intend somehow, verify the characteristics of this social process and the emergency of a new contextualized reality, in other words, public defense working by app. Consequently, we realized that the technology add a new increase to the public service enabling continuity of service and also noticed that the target public of this service are economically fragile people, that had big problems with internet access and management with the technology used, therefore, the mechanism used wasn't enough and good to keep the service quality.